La géographie du collège à l’épreuve des récits - Jean-François Thémines (EchoGéo)
The focus of the debates on the national narrative in history erased the political stakes in the class of geography in the secondary education. The public success of works which propose geographies of France shows nevertheless the interest for the geographical narrative. We analyze the contents of these works and we identify the stakes in the teaching of the French society in geography to the middle school. An ambivalent impression emerges from it. On one side, a professional ethics is possible and it would attempt to think of the disparities produced in and by the teaching of the geography. On the other hand, a school disciplinary reproduction is possible and will not try to think of these disparities.